2018
DOI: 10.33546/bnj.479
|View full text |Cite
|
Sign up to set email alerts
|

Burden Among Family Caregivers of Advanced-Cancer Patients in Indonesia

Abstract: Background: There have been various studies into the family caregivers’ experiences in taking care of advanced-cancer patients. But, a study exploring the burden among family caregivers has not yet been conducted in Indonesia, a country which has strong family bonds among family members.Objective: This present study aimed to identify the burden among family caregivers of advanced cancer patients.Methods: This study was a cross-sectional study conducted from December 2016 to February 2017 on 178 consenting fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
9
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 20 publications
2
9
0
11
Order By: Relevance
“…Penyakit kanker merupakan salah satu penyebab kematian utama di seluruh dunia. Menurut WHO dalam (Sari, Warsini and Effendy, 2018), kanker adalah penyebab kematian tertinggi kedua di negara maju dan tertinggi ketiga di negara berkembang. Pada tahun 2012, sekitar 8.2 juta kematian disebabkan oleh kanker.…”
unclassified
See 2 more Smart Citations
“…Penyakit kanker merupakan salah satu penyebab kematian utama di seluruh dunia. Menurut WHO dalam (Sari, Warsini and Effendy, 2018), kanker adalah penyebab kematian tertinggi kedua di negara maju dan tertinggi ketiga di negara berkembang. Pada tahun 2012, sekitar 8.2 juta kematian disebabkan oleh kanker.…”
unclassified
“…Penelitian terkait family caregiver menjadi penting dikarenakan beban yang dirasakan (fisik, keuangan, psikologis, dan sosial) oleh family caregiver selama merawat anggota keluarganya yang menderita kanker, dan meminimalisasi masalah baru yang akan muncul akibat beban family caregiver yang tinggi dan dapat mempengaruhi kualitas hidup (REFF) family caregiver selama proses perawatan. Masalah baru tersebut adalah kurangnya pemenuhan kebutuhan family caregiver itu sendiri, menurunnya produktivitas kerja, meningkatnya resiko kerentanan terhadapat suatu penyakit, dan bahkan kematian pada family caregiver (Goldstein et al, 2004), (Sari, Warsini and Effendy, 2018), (Effendy et al, 2015). Jika beban family caregiver dapat diidentifikasi dengan baik, maka tenaga kesehatan dapat membantu mengatasi masalah keluarga lebih terarah, sehingga keluarga dapat lebih berfokus pada perawatan pasien lebih lanjut.…”
unclassified
See 1 more Smart Citation
“…They can be the spouse, parents, daughters or sons, or other relatives (Effendy et al, 2014). The studies conducted in East Java (Werdani & Silab, 2020), and Yogyakarta and Central Java (Sari, Warsini, & Effendy, 2018), Indonesia, showed that the patients have their nuclear family as their support system. Taking care of NCD patients has been transformed from curing the disease to offering comfort and a better quality of life.…”
mentioning
confidence: 99%
“…The challenge is that family caregivers spend 24 hours a day helping and assisting patients with their physical and psychological conditions, as well as financial and autonomous problems (Effendy et al, 2014;Machado, Dahdah, & Kebbe, 2018). The study conducted by Sari et al (2018) on 178 family caregivers of advanced cancer patients in Yogyakarta and Central Java showed that the burden was higher for family caregivers who spent more time each day looking after their sick family members.…”
mentioning
confidence: 99%